Efficacy of icotinib in advanced lung squamous cell carcinoma - Shuai Liang; Yan Xu; Fenlai Tan; Lieming Ding; Yongbin Ma; Mengzhao Wang (Cancer Medicine)
Abstract Background There are controversial data supporting the efficacy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in patients with advanced lung squamous cell carcinoma (SCC). In this study, the efficacy of icotinib in unselected and EGFR‐mutated patients with lung SCC was assessed. Methods We retrospectively analyzed the survival time of unselected advanced lung SCC patients treated with icotinib for at least 5 months between June 2013 and June 2016, and selected appropriate EGFR‐mutated advanced lung ADC patients to have 1:1 ratio of propensity score matching with EGFR‐mutated advanced lung SCC patients, and matching factors were age, sex, clinical stage, Karnofsky performance status (KPS), smoking history, EGFR mutation type, and treatment lines. Results A total of 487 unselected advanced lung SCC patients were available for analysis of icotinib treatment efficacy. The progression‐free survival (PFS) was 13.0 months (95% CI 12.2‐13.8), the overall survival (OS) was 16.0 months (95% CI 14.7‐17.3), and the objective response rate (ORR) was 41.3%. After propensity score matching, 78 EGFR‐mutated lung SCC and 78 EGFR‐mutated lung ADC patients were selected and compared. Although no statistical difference was found, ADC patients were associated with a longer PFS (15.8 months vs 12.7 months, P = 0.275) and OS (24.2 months vs 18.5 months, P = 0.150), and a better ORR (59.0% vs 48.7%, P = 0.199) than compared with SCC patients when treated with icotinib. Conclusion Icotinib has a modest therapeutic effect in patients with advanced lung SCC, especially for the population with EGFR mutations.